Constraints to Women’s Use of Public Transport in Developing Countries, Part II : Safety - Borker, Girija (World Bank, Washington, DC, 2022)
Women and men travel differently in low- and middle-income countries and women face different constraints on their mobility. _is Brief is the second in a two-part series that provides an overview of the evidence on key features of women’s travel behavior and the safety barriers they face in accessing public transport in developing countries (see Borker 2022, which focuses on affordability, frequency, coverage, and comfort). This brief focuses on the safety concerns that limit women’s use of public transport, centering on two aspects of safety: safety from accidents and safety from violence. It highlights how women’s different travel behavior, as well as unsafe infrastructure, driving, and vehicle design, make women vulnerable to road accidents. It also shows that an overwhelming majority of women around the world have experienced sexual violence as they travel, whether verbal, visual, or physical. Women’s perceptions about violence and their actual safety in public spaces affect both their physical mobility and economic choices. Understanding the evidence on the challenges faced by women is a first step in identifying policies and interventions that could improve women’s accessibility.